PANIWAK DEWASA SEBAGAI PENENTU DEWASA AYU DI DESA ADAT SELULUNG - I Nyoman Ranem; I Gusti Ngurah Sudiana; I Gede Sutarya (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
The phenomenon that occurs in the Selulung Traditional Village, even though technological developments have spread and become evenly distributed in society in the understanding of dewasa ayu through print and digital media, is that the system for determining dewasa ayu still uses the intermediary of paniwak dewasa (wariga practitioners) through the nunas dewasa tradition. This research aims to analyze and find the reasons why people in the Selulung Traditional Village still use paniwak dewasa in determining dewasa ayu. This research uses qualitative research. The research location in this study is located in Selulung Traditional Village, Kintamani District, Bangli Regency. The technique for determining informants uses purposive sampling technique. The instrument in this research is the researcher himself with research tools such as interview guides, notes, recording devices (cellphones), cameras. Data collection techniques were carried out using observation, in-depth interviews, documentation studies, and literature studies. The data analysis technique is carried out with the stages of data collection, data reduction, data presentation, and data processing which ends with verification and proof. The results of the research show that determining dewasa ayu cannot necessarily be done personally by those who will carry out an activity, but they will ask for guidance from someone who is considered an expert or qualified in their field, which they call the paniwak dewasa.